Role of tyrosol on Candida albicans, Candida glabrata and Streptococcus mutans biofilms developed on different surfaces - Monteiro, Douglas Roberto [UNESP]; Arias, Lais Salomão; Fernandes, Renan Aparecido; Straioto, Fabiana Gouveia; Barbosa, Debora Barros [UNESP]; Pessan, Juliano Pelim [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (My University, 2017)
Purpose: To assess the effect of tyrosol on the production of hydrolytic enzymes (by Candida biofilm cells) and acid (by Streptococcus mutans biofilms), as well as to quantify single and mixed biofilms of these species formed on acrylic resin (AR) and hydroxyapatite (HA). Methods: Candida and S. mutans biofilms were formed on AR and HA in the presence of tyrosol during 48 hours. Next, acid proteinase, phospholipase and hemolytic activities of Candida biofilm cells were determined, while acid production by S. mutans biofilms was assessed by pH determination. The effect of tyrosol on mature biofilms (96 hours) was evaluated through quantification of total biomass, metabolic activity, number of colony-forming units and composition of biofilms' extracellular matrix. Data were analyzed by oneand two-way ANOVA, followed by Tukey's and Holm-Sidak's tests (a = 0.05). Results: Treatments with tyrosol were not able to significantly reduce hydrolytic enzymes and acid production by Candida and S. mutans. Tyrosol only significantly reduced the metabolic activity of single biofilms of Candida species.